(untitled) (Journal of Science and Technology, 2016)
Pharmacological Studies have been carried out on a crude, aqueous extract of Desmodium adscendens, an anti-asthmatic traditional medical remedy in West Africa [1, 2]. In these studies, carbachol-induced contractile response on the guinea-pig tracheal chain, the isolated right atrium of the guinea-pig and antigen-induced bronchoconstriction in the conscious guinea-pig were used. The extract caused a dose-dependent relaxation of the tracheal chain that did not involve fl-adrenoceptor activation. In a few preparations, the effect was biphasic. In the spontaneously beating guinea-pig atrium, the extract produced a depressant effect. On the conscious guinea-pig, the extract had a protective effect on antigen-induced broncho constriction. Com-pared with isoprenaline as a standard bronchodilator drug, however, an aqueous extract of the plant extract was found to be much less potent than the sympathomimetic.